KESEJAHTERAAN SUBJEKTIF PADA MAHASISWA UNIVERSITAS X JAKARTA - Roosdyanto, Fransiskus Xaverius Dwi; Zamralita , Zamralita; Fahlevi , Reza (Fakultas Psikologi Universitas Tarumanagara, 2025)
The transition from secondary school to higher education is a critical phase filled with various academic challenges that may affect students’ subjective well-being, both cognitively and affectively. University students are required to adapt to new learning environments, increasing academic demands, the need for independence, and the pressure to perform optimally. These challenges often impact students' mood, emotions, and overall life satisfaction. Therefore, subjective well-being is an essential component in understanding students' quality of life and their capacity to cope with academic stress. This study aims to describe the subjective well-being of students at University X Jakarta. A descriptive quantitative research method was employed using purposive sampling, involving 114 student participants. The research instrument used was a Likert scale ranging from 1 to 4. The results indicate that students' overall level of subjective well-being is categorized as moderate (63.2%). The mean score for the positive affect dimension was 1.92, the negative affect dimension was 2.46, and the life satisfaction dimension was 2.03. An independent t-test revealed a significant difference in subjective well-being based on gender (Asymptotic Significance 0.048 < 0.05), with female students demonstrating a higher level of subjective well-being compared to male students. These findings imply the importance of developing psychological well-being support services on campus, such as counseling services, stress management programs, and emotional capacity strengthening strategies. Such efforts are expected to help students cope with academic challenges and improve their overall quality of life during higher education.